158 Why can't I win any more?. Issue 3 (9th February 2012) - Dobson, R; Giovannoni, G
Abstract : A 33-year-old gentleman presented with difficulty in playing squash. He was known to have multiple sclerosis (MS). He did not have any physical disability and was a highly ranked squash player. While early in a game he was able to play without difficulty, he developed problems with depth perception during a game and was unable to accurately place the ball. On examination he had mild left-sided optic nerve pallor, consistent with previous optic neuritis. Visual evoked potentials were mildly prolonged, with a visual acuity of 6/6 bilaterally and full colour vision. A clinical diagnosis of exercise/temperature dependent optic nerve dysfunction was made. Transient dysfunction of the optic nerve during exercise is well described in MS. There may be exercise-induced deterioration in MS symptoms in 1/3 patients as a result of increased conduction times in demyelinated axons with a rise in temperature. An impairment of depth perception induced by heat, known as Pulfrich phenomenon, is much less well-described. Pulfrich described a discrepancy in illumination between two eyes causing the illusion that a swinging pendulum is rotating with impaired depth perception. Pulfrich phenomenon is seen in conditions where there is a discrepancy in visual latency between the eyes. Our patient had an increased latency in the left optic nerve that was unmasked by exercise only. Instead of presenting with typical visual blurring, our patients' skill at squash resulted in a unique manifestation.